Analysis of effective capacity for free-space optical communication systems over gamma-gamma turbulence channels with pointing errors - 杨友全 迟学芬 石佳琳 赵琳琳 (Optoelectronics letters, 2015)
To facilitate the efficient support of quality-of-service （QoS） for promising free-space optical （FSO） communication systems, it is essential to model and analyze FSO channels in terms of delay QoS. However, most existing works focus on the average capacity and outage capacity for FSO, which are not enough to characterize the effective transmission data rate when delay-sensitive service is applied. In this paper, the effective capacity of FSO communication systems under statistical QoS provisioning constraints is investigated to meet heterogeneous traffic demands. A novel closed-form expression for effective capacity is derived under the combined effects of atmospheric turbulence conditions, pointing errors, beam widths, detector sizes and QoS exponents. The obtained results reveal the effects of some significant parameters on effective capacity, which can be used for the design of FSO systems carrying a wide range of services with diverse QoS requirements.